Strategi Pendidikan Kristiani dalam Mempresentasikan Injil bagi Anak Sekolah Minggu Prasekolah - Bulanda Agata; Yonatan Alex Arifianto (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2022)
The world of children in preschool is when children are again in the phase of having fun and playing with the family and the outside environment. The preschool age, which is 3-6 years old, is when children enjoy playing while learning. This is a time when children need to be introduced to the education that begins with the knowledge of the truth of God's word from Sunday school activities and introduces them to basic education about the truth of the gospel from the Biblical story. The importance of this research is to cultivate spirituality early for children at preschool age; that is, since children are 3-6 years old, they need a good and correct spiritual life through preaching the gospel and presenting the gospel to children of preschool age. The need for Christian religious education for children at an early age where children need to be reached and introduced to the truth from God's word, to Christ, and children really need guidance from educators, whether they be Christian religious educators, Sunday school teachers or parents also need to play an important role in educating by introducing the truth of the stories in the Bible. Evangelism is one good strategy to reach children by presenting the gospel and the great message in preschool Sunday schools. The purpose of this writing is to find out that strategies in learning Christian religious education are very important for educators, especially for Sunday school teachers, to present the gospel and the great message for Sunday school children in ministry, bringing up creative ideas in teaching strategies. through Sunday school preschool.  Abstrak: Dunia anak-anak dimasa prasekolah merupakan masa di mana anak-anak lagi pada fase senang-senang dan bermain dengan lingkungan keluarga dan lingkungan luar. Diusia prasekolah yaitu umur 3-6 tahun ini adalah masa anak-anak senang dalam bermian sambil belajar. Masa ini adalah masa anak-anak perlu untuk dikenalkan akan pendidikan yang dimulai dar pengenalan akan kebenaran dari firman Tuhan dari kegiatan sekolah Minggu dan mengenalkan kepada mereka pendidikan dasar tentang kebenaran injil dari cerita Alkitab. Pentingnya penelitian ini adalah menumbuhkan kerohanian sejak dini bagi anak-anak diusia prasekolah yaitu sejak anak-anak berumur 3-6 tahun, mereka memerlukan kehidupan kerohanian yang baik dan benar melalui pemberitaan injil, mempresentasikan injil bagi anak-anak usia prasekolah. Perlunya pendidikan agama Kristen bagi anak-anak di usia dini di mana anak-anak itu perlu untuk dijangkau dan dikenalkan akan kebenaran dari firman Tuhan, kepada Kristus, dan anak sangat perlu pembinaan dari para pendidik entah itu pendidik agama Kristen, guru sekolah Minggu maupun orang tua juga perlu berperan penting untuk mendidik dengan mengenalkan akan kebenaran dari cerita yang ada didalam Alkitab. Penginjilan adalah salah satu strategi yang baik untuk dilakukan supaya bisa menjangkau anak-anak dengan mempresentasikan injil dan amanat agung disekolah Minggu prasekolah. Tujuan dari penulisan ini adalah mengetahui bahwa strategi dalam pembelajaran pendidikan agama Kristen sangat penting untuk para pendidik terutama bagi guru sekolah Minggu untuk dapat mempresen-tasikan injil dan amanat agung bagi anak-anak sekolah Minggu dalam pelayanan, memunculkan akan ide-ide kreatif dalam strategi pengajaran melalui sekolah Minggu prasekolah.